Prediction and analysis of disease burden of mental disorders in China from 1990 to 2021 - JIANG Lu; ZHANG Zhidong; WU Jianjun; LIU Lu; SHANG Longjian; WEI Xingmin (Yixue xinzhi zazhi)
Objective To analyze the disease burden of mental disorders in China from 1990 to 2021 and to predict the incidence of mental disorders from 2022 to 2032.Methods The Joinpoint model was applied to analyze the trend of the incidence of mental disorders by using the Global Burden of Disease Study database in 2021, and the annual percentage change (APC) and average annual percentage change (AAPC) were calculated. The age-period-cohort model was used to analyze the effects of age, period and cohort on mental disorders, and predict the incidence of mental disorders in 2022—2032.Results In 2021, the age-standardized incidence rates ASIR of mental disorders in the total population, males, and females were 3,349.58/100,000, 2,822.50/100,000 and 3,876.57/100,000, respectively. From 1990 to 2021, the ASIR of mental disorders in Chinese total population [AAPC=-0.17%, 95%CI(- 0.34%, -0.03%)] and women [AAPC=-0.33%, 95%CI(-0.55%, -0.11%)] showed a decreasing trend, while the incidence among men fluctuated. The results of the age effect showed that the incidence of mental disorders among Chinese residents increased, then decreased and then increased again as age increased. The period effect results showed that the risk of mental disorders in Chinese residents from 1990 to 2021 showed a trend of first decreasing and then increasing over time. The results of the birth cohort showed that the risk of mental disorders in Chinese residents increased first, then reduced, and then increased with the transition of birth cohort. The predicted results show that the ASIR of mental disorders in China will show a downward trend from 2022 to 2032.Conclusion From 1990 to 2021, although the incidence of mental disorders in Chinese residents decreased overall, adolescents, middle-aged and elderly people and females are still the focus of prevention and control of mental disorders. In the future, the mental health of adolescents, middle-aged and elderly and female should be pay more attention.